Book review - Szefer, Agnieszka (Studies in Second Language Learning and Teaching, 2012)
Sally Meets Harry: Practical Primer to English Pronunciation and Spelling Author: Marta Nowacka, Piotr Cymbalista and Grzegorz A. Kleparski Publisher: Wydawnictwo Uniwersytetu Rzeszowskiego ISBN: 978-837-33867-3-0 Pages: 208; How Much Wood Would a Woodchuck Chuck?’ English Pronunciation Practice Book Author: Anna Mańkowska, Marta Nowacka and Magdalena Kłoczowska Publisher: Konsorcjum Akademickie ISBN: 978-839-28763-2-8 Pages: 200.